2009
DOI: 10.1002/iroh.200911149
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation and Preliminary Chemical Characterization of Microcystis Exopolysaccharides from a Cyanobacterial Water Bloom of Lake Taihu

Abstract: A bloom biomass composed mainly of Microcystis spp. was harvested from Lake Taihu, China. Exopolysaccharides (FEPS, exopolysaccharides from field-grown Microcystis spp.) were extracted from the bloom mass with 3% glutaraldehyde. FEPS contained 5.4% protein and 6.9% uronic acid (glucuronic acid and galacturonic acid). The neutral sugar composition of FEPS consisted of rhamnose, arabinose, mannose, glucose and galactose in a relative molar ratio of 4.8 : 4.2 : 2.1 : 3.7 : 1.0, respectively. The di alyzed FEPS ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It was previously observed that polysaccharides were secreted during frequent and extensive bloom events in lakes dominated by colony‐forming Microcystis (Li et al. ). A recent study reported that colonial Microcystis could secret more soluble polysaccharides into the medium than the unicellular form (Zhang et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was previously observed that polysaccharides were secreted during frequent and extensive bloom events in lakes dominated by colony‐forming Microcystis (Li et al. ). A recent study reported that colonial Microcystis could secret more soluble polysaccharides into the medium than the unicellular form (Zhang et al.…”
Section: Discussionmentioning
confidence: 97%
“…We have shown in this study that colonial Microcystis possesses the advantage of physiological acclimation over the unicellular form when growing under iron-deficient conditions. It was previously observed that polysaccharides were secreted during frequent and extensive bloom events in lakes dominated by colony-forming Microcystis (Li et al 2009). A recent study reported that colonial Microcystis could secret more soluble polysaccharides into the medium than the unicellular form ).…”
mentioning
confidence: 97%
“…On the contrary, the presence of deoxy sugars rhamnose and fucose in side chains, which are known for their hydrophobic properties due to the methyl group at carbon 6, increases the hydrophobicity and stickness of the extracellular polysaccharide of A. granulate (VIEIRA et al, 2008). The predominance of rhamnose may increase the hydrophobic feature of the extracellular polysaccharide of Microcystis (LI et al, 2009). Further studies on chemical structure of extracellular polysaccharide in Microcystis are urgent to be performed in order to elucidate the function of extracellular polysaccharide in cell hydrophobicity.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Microcystis, the position relative to the surface can be achieved thanks to the presence of gas vesicles aggregations or aerotopes in the cytoplasm (Šmarda and Maršálek, 2008), which allow them to regulate their vertical position in the water column and to form the colony in a suitable position receiving the right amount of light, oxygen and CO2. The EPS matrix of bacteria that are able to form pellicles are usually composed by glucose, galactose, rhamnose, mannose or cellulose (for a review see Armitano et al 2014), which are also typical components of the extracellular matrix of Microcystis (Lei et al, 2007;Li et al, 2009). Thus, Microcystis colonies have more than one trait contributing to float near the surface.…”
Section: Main Characteristics Of Bacterial Biofilmsmentioning
confidence: 99%